TECHNICAL ADVANTAGE OF BI-CURRENT SYSTEM OF DISTRIBUTED GENERATION - KIMSTACH, OLEG; CHUMAK, MYKOLA (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The paper discusses two circuit types of a distributed generation system for supplying power energy to private households. The first of them is called a mono-current system and it is a combined distributed generation system based on solar panels and a wind generator with power supply to AC loads. The second is called a bi-current system because it has two separate power distribution systems for AC and DC. The paper provides their functional and circuit descriptions, as well as a qualitative comparative analysis. The main goal of the work is to prove the technical advantage of the bi-current system. This problem is solved using the method of relative comparative estimates. The number of transformation elements and the generalized efficiency of the power circuit were selected as comparison criteria.As you know, for any system the cost is higher and reliability is lower, than its number of elements is more. It has been defined that during the flow of electrical power from sources to loads in a bi-current system, in general, half as many transformation elements are overcome as in a mono-current system. For any system the operating costs are lower, if the efficiency is higher. When calculating the generalized efficiency, only the power circuit was taken into account, since it is the most power-intensive circuit. The calculation was also performed for a stationary mode close to the nominal one. Such assumptions do not allow us to accurately calculate the quantitative values of efficiency, but they allow us to perform a preliminary qualitative comparative analysis. The paper presents algorithms for calculating the efficiency of both systems. An example calculation showed that the efficiency of the bi-current system is approximately 6% higher.As a result of the research, it was found that the resulting relative estimate of the bi-current system is higher by approximately a quarter of a point, which indicates its clear advantage. Thus, the technical advantage of the bi-current system has been proven, so it is a more promising circuit solution for distributed generation systems.
Keywords: distribution generation; mono-current system; bi-current system; power circuit; method of relative comparative estimates